A polícia comunitária em Mato Grosso : tensão entre estado e sociedade - Silva, Sebastião Carlos Rodrigues da (2018)
The tensional relationship between state and society has been constant throughout human history and governments aim to strengthen the relationship with society, which has been increasingly demanding. Community police are an example of this attempt. The present study sought to analyze the implementation of the community police project in Cuiabá, in order to identify the degree to which society participed and if there is in Cuiabana society the necessary preconditions for implementation and support of the project. We start with a criticism of Michael Oakeshott on Constructivist rationalism. The preconditions relate to Community social capital. The problem is to know the degree of adequacy between the prerequisites of the community police model implemented in Cuiabá and the degree of citizenship (social capital) of the population. The hypothesis is that at the base of the Cuiaban society there is no civic prerequisite for the effectiveness of the community policing, Michel Foucault’s ponoptic survellance, Robert Putnam’s social capital, Alexis de Tocquevilles’s (as associativism). The research method is qualitative-quantitative, with the abductive research strategy. The field research had as its delimitation — community leaders, population of voters residing in neighborhoods that have the project Community Police implanted and public managers. The collection instruments used were the survey, the focus group interview and the semi-structured interview. The results show that at the base of Cuiaban society there is not enough social capital to implement and consolidate the project and that the community police model resembles a model of problem solving policing.